2022
DOI: 10.4236/ojpp.2022.123026
|View full text |Cite
|
Sign up to set email alerts
|

Reincarnation as a Complement to the Flawed DNA-Based Model of Life: Potential Contributions to Our Disposition towards Family and Religion/Spirituality

Abstract: Briefly summarized here are some reasons why the DNA/genetic model of life appears to be inadequate (for more details see previous OJPP paper). Given its foundational role with regards to our understanding of life and its challenges, this is significant. The traditional dualistic reincarnation model is introduced. That model is then considered, along with the DNA model, as potential explanations for our natural religious instincts. Next, the two models are considered as possible bases for the phenomenon of kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Previous work by the author has suggested that the traditional reincarnation model appears to be a good starting point to explain some mysteries including the general missing heritability (Christopher, 2017a;Christopher, 2017b). Additional work in this journal considered some evolutionary phenomena and their possible transcendental-based explanations (Christopher, 2022a;Christopher, 2022b). A reincarnation (or transcendental) approach would also be consistent with dualism (as argued in the above-cited works by Stevenson, Tucker, and Carter).…”
Section: Discussionmentioning
confidence: 84%
“…Previous work by the author has suggested that the traditional reincarnation model appears to be a good starting point to explain some mysteries including the general missing heritability (Christopher, 2017a;Christopher, 2017b). Additional work in this journal considered some evolutionary phenomena and their possible transcendental-based explanations (Christopher, 2022a;Christopher, 2022b). A reincarnation (or transcendental) approach would also be consistent with dualism (as argued in the above-cited works by Stevenson, Tucker, and Carter).…”
Section: Discussionmentioning
confidence: 84%
“…Previous work by the author has suggested that the traditional reincarnation model appears to offer a good starting point to explain some mysteries including the general missing heritability problem (Christopher, 2017a(Christopher, , 2017b. Additional work in this journal considered some evolutionary phenomena and their possible reincarnation-based explanations (Christopher, 2022a(Christopher, , 2022b. Furthermore, beyond this there seem to be numerous other amazing-and under-appreciated-mysteries.…”
Section: Discussionmentioning
confidence: 99%
“…Secondarily, materialism appears inadequate to describe a number of unusual but accepted behavioral phenomena, including those of prodigies (Christopher, 2020). Of more general significance, our innate religious belief package strains the plausibility of evolutionary/DNA origins (Christopher, 2022b;Barrett, 2012).…”
Section: Introduction-the Landscape Of Materialism and Neurosciencementioning
confidence: 99%
“…Questions abound surrounding our innate spiritual beliefs including of course the belief in a design impact but perhaps if the intervening stage (in a sequential life dynamic) involved psyche projections (as in dreaming) (Fremantle & Trungpa, 1992;Carter, 2012;Christopher, 2022b) that might contribute to a young child's belief in designs. One test of that hypothesis could come with investigations of natural religion around the globe.…”
Section: Discussionmentioning
confidence: 99%